Market research of medicinal products which are used in cardiological diseases treatment - O. S. Kukhtenko; L. S. Simonyan; Ye. V. Hladukh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2017)
Aim of the study is to carry out market research of medicinal products which are used in cardiological diseases treatment.